Navigating the clinical ambiguity of implant placement in two young pubescent patients: an insight from two case reports - Wilson, Teena; Nair, Vivek V; Harsha Kumar, K; Kala, S (International Journal of Dental Materials, 2023)
The horizon of implant dentistry has been ever-expanding owing to its long-term success in rehabilitating partially or completely edentulous cases. This perennial success and efficiency have encouraged clinicians to use osseo-integrated implants to replace teeth lost in children either due to trauma or congenital absence. Although a myriad of studies and publications suggest the placement of implants only after the attainment of skeletal maturity, as the growth-related changes such as remodelling, displacement, and mesial drift can put the future of implant and restoration in jeopardy, the use of implants in young pubescent or adolescent looks promising due to its evident psychological and social advantages over other contemporary alternatives such as a removable prosthesis or resin-bonded bridge. The first case report highlights a 16-year follow-up of a young girl treated at the age of 10 with an implant-supported prosthesis for the replacement of a missing maxillary left central incisor. The second case report centers around a 19-year-old teenage girl who underwent rehabilitation with a permanent fixed prosthesis, replacing her previous implant-supported temporary prosthesis. The implant was initially placed when she was 10 years old.